COMPLEX RHEABILITATION INCLUDING BOTULIN TOXIN A INJECTIONS IN PATIENTS WITH INFANTILE CEREBRAL PALSY – INFLUENCE ON PHYSICAL AND MOTOR DEVELOPMENT - E.A. Kislyakova (Педиатрическая фармакология)
Infantile cerebral palsy (ICP) is an important medical and social problem, associated with high prevalence and disability rates. The efficacy of rehabilitation was evaluated in 38 patients with ICP. The complex rehabilitation consisted of massage, physiotherapy, therapeutic physical training, the method of dynamic proprioceptive correction using gravistat and adely therapeutic devices, traditional and laser acupuncture and botulin toxin a injections, which were used in 10 patients with symmetric neck:righting reflex. botulin toxin a was injected in m. pectoralis major. The efficacy was based on dynamic evaluation of physical and motor development regarding age, disease severity and injection route of botulin a toxin. Key words: infantile cerebral palsy, rehabilitation, botulintoxin a, physical and motor development